Plasma Hormones, Lipid Profile and Productive Performance During Early Lactation in Crossbred Cows Supplemented with Prilled Fat - Gnanasekar, Rajesh; Singh, Mahendra; Roy, Ashwani Kumar; H.M., Ajithakumar; Thakur, Sunita (Indian Journal of Animal Nutrition, 2018)
Twelve crossbred Karan Fries cows were divided into 2 groups viz., control (CON) and supplemented group (SG) based on milk yield (16.60 vs. 16.45 kg/d) and days in milk (20.01 vs. 21.0 days). The SG cows were fed prilled fat @ 75 g/d/animal from day 30 to 120 days of lactation. Body weight and body condition score were recorded. Plasma hormones and lipid profile were estimated at fortnightly intervals. Feeding of prilled fat did not influence feed intake, plasma prolactin, insulin, cortisol, T3 and T4 levels. The supplementation of prilled fat increased plasma triglycerides level (P<0.05) and decreased plasma HDL (P<0.05) in SG in comparison to CON group. Milk yield increased (P<0.05) by 6.03% concomitant to increase in body weight and BCS in SG over the control group cows. However, milk cholesterol level remained unchanged. The supplemented cows exhibited earlier resumption of estrous cyclicity and improved conception rate. It was concluded that supplementation of prilled fat enhanced productive performance by restricting mobilization of body reserves without affecting feed intake, plasma hormones and lipid profile in crossbred cows.